A continuum large-deformation theory for the coupled modeling of polymer–solvent system with application to PV recycling. (1st June 2023) - Liu, Z.; Marino, M.; Reinoso, J.; Paggi, M.
Abstract: Nowadays recycling of photovoltaics (PV) using the solvent method is becoming a very hot topic as massive products deployed in the last century have approached the end of their service lifetime. The key problem in the recycling of end-of-life PV modules is the nondestructive recovery of precious silicon wafers for the manufacturing of new products. However, the attempt to comprehensively understand the polymer–solvent system in the PV recycling process is completely lacking. In this work, a thermodynamically consistent large-deformation theory is proposed to model the coupled behavior of this system. The development of continuum theory accounts for the solvent permeation, swelling and elastic deformation, as well as shrinking effects due to the initial crosslinking of ethylene-co-vinyl acetate (EVA). The crosslinking of EVA influences the stiffness of the polymer network, and interacts with the diffusive kinetics of solvents. Also, given the effects of mechanical constraint, the two-way coupling between the EVA deformation and solvent diffusion is established on the basis of thermodynamic arguments. The proposed modeling method is firstly applied to simulate the swelling experiments of cylindrical EVA samples in solvents Toluene, Tetrahydrofuran, and Octane, and good agreement has been achieved between the numerical prediction and available testing data. Then the second example demonstrates the capability of this modeling framework to describe the influences of initial crosslinking and mechanical constraints on the time history evolution of swelling and elastic deformation. Finally, the complete PV laminate in the 3D setting is modeled for the investigation of solvent penetration induced deformation in the silicon cell layer during the PV recycling process, and comparison has been made to showcase the spatial distribution of maximum principal stress of the silicon cell layers in solvents with different solubility parameters and molar volumes. With this computational tool at hand, it is possible to provide guidance to the design of suitable experimental procedures for the structure-intact recovery of silicon wafers in PV recycling with the solvent method.